A Policy Framework for Institutional Nutrition and Well-Being Support Among Adolescent Athletes in Philippine Schools - Fadare, Stephen A.; Juhn-Agsak, Tawita S.; Edris, Aloy B.; Oyda, Ariel; Pangandaman, Hamdoni K.; Langcoy II, Roque N. (Futurity Medicine, 2026)
Aims: Adolescent athletes navigate a demanding mix of physical growth, academic responsibilities, and intense sports training—making their nutritional needs uniquely complex. Although research clearly highlights the connection between good nutrition, athletic performance, and mental health, most schools in the Philippines and around the world still lack thorough, organized systems to support student-athlete well-being. Methodology: This policy review analysis draws on international best practices and identifies persistent gaps in current approaches, especially within the Philippine education system, where informal advice, limited staff training, and food insecurity remain common issues. Using a seven-pillar framework—encompassing structured nutrition services, staff development, mental health integration, supplement regulation, equitable food access, sport-specific curriculum, and accountability — this study calls for a shift from relying on individual initiative to building strong institutional support. Results: The findings emphasize that nutrition and well-being must be at the core of school policy and equity efforts. Recommendations include establishing dietitian-led services, forming interdisciplinary wellness committees, and creating scalable solutions for resource-limited schools. Conclusion: By closing the gap between policy and practice, Philippine schools can foster environments where every adolescent athlete can achieve their full potential. Ultimately, treating nutrition and well-being as essential governance issues is vital for building a healthier, more resilient generation of youth athletes.